MANAJEMEN ZAKAT DI YORDANIA: SISTEM, KELEMBAGAAN, DAN DAMPAK SOSIAL EKONOMI - Riski Sahyuri; Maryam Batubara (Smart Education, 2026)
Abstract: This study aims to comprehensively analyze zakat management in Jordan by highlighting the institutional system, management mechanisms, and its impact on socio-economic conditions. The research adopts a qualitative approach using a literature review method based on secondary sources such as scientific journals, official reports, and academic literature. The findings indicate that zakat management in Jordan is semi-formal, as it operates within a government regulatory framework but is not fully mandatory, making its implementation largely dependent on individual awareness. Institutionally, zakat is managed by a national body in collaboration with local committees, creating synergy between the government and the community in the collection and distribution processes. In practice, zakat is not only distributed in a consumptive form to meet basic needs but is also developed through productive programs such as microfinance and skills training to enhance the economic independence of beneficiaries. This management has contributed to poverty reduction and improved social welfare, although it is not yet optimal. This is due to the underutilized potential of zakat collection and the distribution still being dominated by consumptive assistance. Therefore, stronger regulations, improved transparency, and innovative empowerment-based programs are needed to optimize the role of zakat as a social welfare instrument in Jordan. Keywords: Zakat Management, Jordan, Institutional System, Social Impact, Poverty Reduction Abstrak: Penelitian ini bertujuan untuk menganalisis secara komprehensif manajemen zakat di Yordania dengan menyoroti sistem kelembagaan, mekanisme pengelolaan, serta dampaknya terhadap kondisi sosial ekonomi masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kepustakaan melalui berbagai sumber sekunder seperti jurnal ilmiah, laporan resmi, dan literatur akademik. Hasil penelitian menunjukkan bahwa pengelolaan zakat di Yordania bersifat semi formal karena berada dalam kerangka regulasi pemerintah namun tidak sepenuhnya bersifat wajib, sehingga pelaksanaannya masih bergantung pada kesadaran individu. Secara kelembagaan, zakat dikelola oleh lembaga nasional yang bekerja sama dengan komite lokal, menciptakan sinergi antara pemerintah dan masyarakat dalam penghimpunan dan pendistribusian. Dalam implementasinya, zakat tidak hanya disalurkan dalam bentuk konsumtif untuk memenuhi kebutuhan dasar, tetapi juga dikembangkan melalui program produktif seperti pembiayaan usaha mikro dan pelatihan keterampilan guna meningkatkan kemandirian ekonomi mustahik. Pengelolaan zakat ini terbukti berkontribusi terhadap penurunan tingkat kemiskinan dan peningkatan kesejahteraan masyarakat, meskipun belum optimal. Hal ini disebabkan oleh potensi penghimpunan zakat yang belum dimaksimalkan serta distribusi yang masih didominasi bantuan konsumtif. Oleh karena itu, diperlukan penguatan regulasi, peningkatan transparansi, serta inovasi program berbasis pemberdayaan ekonomi agar zakat dapat berfungsi lebih optimal sebagai instrumen kesejahteraan sosial di Yordania. Kata Kunci: Manajemen Zakat, Yordania, Sistem Kelembagaan, Dampak Ssosial, Pengetasan Kemiskinan